Collin Hamlin: capstone - Hamlin, Collin, artist (Colorado State University. Libraries, 2022)
The artist's statement: Hello to whoever is reading this at some point in the future. My name is Collin Hamlin. When I was young, I did not have an easy life. Things where hard and Imagination and play, toys and tv, where my outlets to find peace. Escapism became my coping mechanism, turning to worlds I could engineer to my liking. I remember summer days of sitting in my old bedroom imagining the house was a continent, and each room was like a province full of characters and histories.Toy lines like Lego's Bionicle captivated me with it's cinematic marketing and stylistic box art and character design. Shows like Avatar the Last Airbender drew me in with deep characters and fantastic worlds. As I grew older, these aspects of characters and cinematic story-like advertising became a key part of my art. I became dedicated to bringing characters to life, and making things look epic. Trying to provide a sense of escapism for myself and others by painting joy atop the stressful mundanity of life. Even in the most typographic of my works, you can still find some element of personality and character design. I enjoy working on projects with some form of story or style to it. Things that could be interactive, or things that you can actually hold interest me the most. I suppose after saying all this, I just enjoy making. Exploring what I can make and trying to bring a small sense of play into the world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design